Acute Effects of Pyrethroids on Serotonin Release in the Striatum of Awake Rats: An In Vivo Microdialysis Study. Issue 2 (6th November 2012) - Hossain, Muhammad M.; Suzuki, Tadahiko; Richardson, Jason R.; Kobayashi, Haruo; Slitt, Angela L.; Hodgson, Ernest
ABSTRACT The present study examined the acute neurotoxic effects of three different pyrethroids, allethrin, cyhalothrin, and deltamethrin on the release of serotonin (5‐HT) and its metabolite 5‐hydroxyindoleacetic acid (5‐HIAA) in the striatum of conscious rats using microdialysis. Allethrin 10 mg/kg reduced extracellular levels of 5‐HT to 46%, whereas 20 and 60 mg/kg increased the release to 177% and 243% of baseline, respectively. Cyhalothrin increased 5‐HT release to 145–204% and deltamethrin decreased to 58–32% of baseline in a dose‐dependent manner. None of the pyrethroids tested altered extracellular levels of 5‐HIAA. Local infusion of the voltage‐gated sodium channel antagonist tetrodotoxin (TTX) into striatum completely prevented the effects of allethrin, cyhalothrin, and deltamethrin (10 and 20 mg/kg) on 5‐HT release. The effect of deltamethrin at 60 mg/kg was completely abolished by striatal infusion of nimodipine (L‐type Ca++ channel antagonist) with TTX. These findings suggest that pyrethroids disrupt the serotonergic neurotransmission in striatum in a dose‐related manner with Na+ and Ca2+ channel‐dependent mechanisms. © 2012 Wiley Periodicals, Inc. J BiochemMol Toxicol 27:150‐156, 2013; View this article online at wileyonlinelibrary.com. DOI 10.1002/jbt.21450